APPROPRIATE CARE AND TREATMENT IN OUR NEIGHBORHOODS (ACTION): AN INTERDISCIPLINARY TEAM INTERVENTION. (16th November 2018) - Dragan, D; Albright, A; Gregg, A; Parish, S; Crowther, M; Friend, R; Crawford, W
Abstract: Approximately 80% of adult visits to the emergency room are due to lack of access to other providers (CDC, 2012). ACTION is an interdisciplinary team including a nurse practitioner, psychology graduate students, paramedics, and social workers who respond to 911 calls with fire department paramedics. On scene, ACTION performs assessments to determine the most appropriate source of treatment and provides a better option of care to patients who do not need ambulance transport or emergency department care. Adult patients treated by ACTION are contacted to participate in a follow-up assessment of their perceptions of care quality using a modified version of the HCAHPS survey. In an ongoing pilot study, 36 patient encounters have occurred. Patients are aged 16 to 85 years; 34% identified Medicare as their primary insurance provider; 22% had a behavioral health condition as primary diagnosis. Primary diagnoses of patients include: headache, diabetes, influenza, stomach pain, ankle sprain, anxiety, depression, dementia, and more. 20 participants were eligible to be contacted for follow-up interviews. Of these, 4 people refused to participate, 9 were unable to be contacted, and 7 completed the follow-up assessment. For all 911 calls, providers document the needs of the call and the interdisciplinary responder team interactions. Current assessment of the intervention indicates an estimated total cost savings of $2, 491 per patient encounter and suggests a gap exists in public knowledge related to utilizing 911 services. The ACTION team offers a potential intervention to address this gap.